2021
DOI: 10.21203/rs.3.rs-915419/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of The Peripherally Acting µ-Opioid Receptor Antagonist Methylnaltrexone On Acute Pancreatitis Severity: Study Protocol for a Multicentre Double-Blind Randomised Placebo-Controlled Interventional Trial, The PAMORA-AP Trial

Abstract: Background: Moderate to severe acute pancreatitis (AP) is associated with a high rate of complications and increased mortality, yet no targeted pharmacologic treatment currently exists. As pain is a dominant symptom in AP, patients are exposed to excess levels of both endo- and exogenous opioids, which may have harmful effects on the course of AP. This trial investigates the effects of the peripherally acting µ-opioid receptor antagonist (PAMORA) methylnaltrexone on disease severity and clinical outcomes in pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Opioids also increase gut transit time which can cause bacterial overgrowth that can cause pain and bloating. Preclinical studies have shown that opioids can increase intestinal permeability, which is known to increase the translocation of bacteria and the risk of local and systemic infections, which might be promoted by opioid-induced immunosuppression [27]. It is customary to treat opioid induced intestinal dysmotility with laxatives although there is little evidence for r which specific laxative is most effective.…”
Section: Strong Opioidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioids also increase gut transit time which can cause bacterial overgrowth that can cause pain and bloating. Preclinical studies have shown that opioids can increase intestinal permeability, which is known to increase the translocation of bacteria and the risk of local and systemic infections, which might be promoted by opioid-induced immunosuppression [27]. It is customary to treat opioid induced intestinal dysmotility with laxatives although there is little evidence for r which specific laxative is most effective.…”
Section: Strong Opioidsmentioning
confidence: 99%
“…It is customary to treat opioid induced intestinal dysmotility with laxatives although there is little evidence for r which specific laxative is most effective. Recognizing that endogenous opioids, released in response to pain and visceral injury, also contribute to dysmotility means that laxatives might be required even when opioids are not prescribed [27]. There appears to be a role for peripherally acting mopioid receptor antagonists that have been shown to be effective in treating postoperative ileus and chronic constipation that share common mechanisms to that seen in opioid induced intestinal dysmotility [28].…”
Section: Strong Opioidsmentioning
confidence: 99%